2021
DOI: 10.1186/s40345-021-00230-8
|View full text |Cite
|
Sign up to set email alerts
|

Lurasidone in the long-term treatment of Japanese patients with bipolar I disorder: a 52 week open label study

Abstract: Background The current study evaluated the long-term (52 week) safety and impact on symptom measures of lurasidone (with or without lithium or valproate) for the treatment of bipolar I disorder in Japanese patients. Methods Bipolar patients for this open-label flexibly dosed lurasidone (20–120 mg/day) study were recruited from those with a recent/current depressive episode who completed an initial 6 week, double-blind, placebo-controlled, lurasidon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In a one-year study in Japan, including BD patients, the drug was used in the same doses as above, with or without lithium or valproate. It was shown that in previously treated patients with bipolar depression, the drug continued the betterment in depressive symptoms and also improved psychiatric conditions in patients with manic, hypomanic, or mixed episodes [69]. Therefore, it seems that lurasidone may successfully meet the criteria for becoming an SGMS.…”
Section: Lurasidonementioning
confidence: 98%
“…In a one-year study in Japan, including BD patients, the drug was used in the same doses as above, with or without lithium or valproate. It was shown that in previously treated patients with bipolar depression, the drug continued the betterment in depressive symptoms and also improved psychiatric conditions in patients with manic, hypomanic, or mixed episodes [69]. Therefore, it seems that lurasidone may successfully meet the criteria for becoming an SGMS.…”
Section: Lurasidonementioning
confidence: 98%
“…Lurasidone (20-80 mg/day) combined with lithium or valproate showed a better prophylactic effect on bipolar I disorder than lurasidone placebo [ 79 ]. In a most recent 52-week study of Japanese patients with bipolar disorder, lurasidone at 20-120 mg/day, with or without lithium or valproate, maintained improvements in depressive symptoms for previously treated bipolar depressed patients and led to improvements in manic symptoms among a newly recruited subgroup of patients with a recent/current manic, hypomanic, or mixed episode [ 80 ].…”
Section: Application Of Third-generation Antipsychotics Drugsmentioning
confidence: 99%
“…A DBRCT (n = 211) in major depressive disorder with hypomanic features showed lower rates of parkinsonism (2.8%) and akathisia (3.7%) than similar studies in bipolar depression [ 64 ]. A year-long open label study (n = 199) of lurasidone in maintenance BPD treatment demonstrated akathisia in 30.7% and parkinsonism in 7.5% of treated individuals with 4% of individuals discontinuing treatment for akathisia [ 65 ].…”
Section: Incidence Of Dimd With Novel Antipsychoticsmentioning
confidence: 99%